Microfinance as facilitator for achieving the SDGs: A Systematic Literature Review (European journal of volunteering and community-based projects, 2024)
The objective of this research is to verify how microfinance can help achieve the SDGs. The objective is pursued through a systematic analysis of the literature and by answering the two identified research questions. The article uses a structured review of international literature through the Scopus database to identify articles and subsequently the analysis is carried out using MySRL and Bibliometrix software. After having analyzed the content of the 17 Sustainable Development Goals, with particular attention to inclusive finance and microfinance, the systematic analysis of the literature highlights how important sustainability is for microfinance. To the extent of our knowledge, we did not find any systematic literature review addressing this topic.
Keywords: Microfinance; SDGs; Financial Inclusion; Sustainability